Millenials Endorse Environment Factors as Continuance Intention of the Mobile Payment Technology During Covid-19 in Indonesia - Dewi Tamara; Catherine Widjaja; Fellia Elista; Sarah Yassar (Kusuma Negara Business School, 2021)
The purpose of this paper is to determine the effect of additional value, government support and system quality as environmental factors towards continuance intention of mobile payment during COVID-19 in Indonesia through satisfaction as a mediating variable. The study highlights how environmental factors can increase millennials' satisfaction in using mobile payments intention during COVID-19. Data were collected from 268 mobile payment users who transact more than three times a week using a purposive sampling approach through a questionnaire. This study uses SEM with SmartPLS software. The results showed that user satisfaction as a mediation significantly influenced the continuance intention of mobile payment during COVID-19. User satisfaction is directly influenced by environmental factors, which contained additional value, government support, and system quality. Moreover, system quality shows the most significant influence followed by additional value and government support. This study only focuses on the millennial generation in Indonesia, where the use of mobile payments is not only used by the millennial generation. This study also only focuses on conditions during the COVID-19 pandemic. This study proposed a research model adapted from the Technology Continuance Theory (TCT) and Technological Personal Environmental (TPE) models to measure the continuance intention of mobile payments. This study provides insight that environmental factors such as additional value, government support, and system quality can increase customer satisfaction and the continuance intention to use mobile payments. In addition, this study also provides insights for related parties such as mobile payment service providers, the government, and network operators in optimizing mobile payment services.